+0

# algebra

0
92
2

Solve $a = 3 + \sqrt{5a - 9}$ and $b = 1 + \sqrt{5b - 5}$.

Mar 22, 2021

#1
+1

a  =  3  +  sqrt ( 5a - 9)

a - 3  = sqrt (5a - 9)          square both sides

(a - 3)^2  = 5a  - 9

a^2  - 6a  +  9  =  5a  - 9             subtract 5a,  add 9   to both sides

a^2  - 11a + 18  =  0             factor

(a  -  9) ( a - 2)  =  0

Setting  both  factors   to  0   and solving for   a  gives  that

a = 9            or      a  = 2

Check  9                                                      Check 2

9  = 3  + sqrt ( 5*9 - 9)                               2  =  3  +  sqrt ( 5*2 - 9)

9  = 3  +  sqrt (36)                                      2  =  3  +  sqrt !

9  = 3 + 6                                                    2  =  3 + 1

good                                                           2  = 4

no good

So....the only answer  is    a  =  9   Mar 22, 2021
#2
+1

The second one is similar

b - 1  = sqrt ( 5b - 5)             (1)

(b - 1)^2  = 5b - 5

b^2  - 2b  +  1  =  5b  - 5

b^2 - 7b + 6  = 0

(b - 6)  ( b - 1)  =  0

b= 6     or  b  =1

Note  that BOTH solutions will  work, here.....check them in (1)  and see   Mar 22, 2021